Voltage control loss factors for quantifying DG reactive power control impacts on losses and curtailment. Issue 10 (2nd February 2022) - Deakin, Matthew; Morstyn, Thomas; Apostolopoulou, Dimitra; McCulloch, Malcolm D
Abstract: Distributed Generators that use reactive power for voltage control in distribution networks reduce renewable curtailment but can significantly increase network losses, undermining the effectiveness of this control. This paper proposes Voltage Control Loss Factors (VCLFs) as a means of understanding the interactions between reactive power flows, losses and curtailment, focusing on commercial‐scale generators in radial systems. The metric uses a substitution‐based method, whereby a system with voltage control is compared against a counterfactual with no such control. The proposed method studies this metric by coupling numerically precise black‐box simulations with analytic results from a Two‐Bus network representation. The latter provides a physical explanation for the numerical simulation results in terms of power, voltage and impedance parameters, providing clear explainability which is absent in traditional approaches for determining distribution loss factors. The whole solution space of the Two‐Bus system is explored, and VCLFs are calculated for six cases on three unbalanced test networks to illustrate the approach. Relative losses as high as 30% are found in a system with high branch resistance‐reactance ratio and large voltage rise. The results have implications for the design of loss allocation algorithms in distribution networks, and the optimal sizing of power‐electronic interfaced Distributed Generators.